1998
DOI: 10.1111/j.2044-8295.1998.tb02699.x
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of office‐related tasks by speech and office noise

Abstract: Three experiments examine what is widely reported to be one of the most common forms of interference in open‐plan office environments—the effect of background noise. Experiment 1 investigates whether office noise (with or without speech) is disruptive to two office‐related tasks: memory for prose and mental arithmetic. The results show that whereas office noise with speech disrupts performance on both tasks, office noise without speech disrupts performance on the mental arithmetic task only. Experiment 2 inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
199
8
5

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 222 publications
(227 citation statements)
references
References 19 publications
15
199
8
5
Order By: Relevance
“…In general, these results stand in contrast to previous work showing that the effects of auditory interference is different for extraverts and introverts (e.g., Banbury & Berry, 1998;Belojevic et al, 2001;Cassidy & MacDonald, 2007;Daoussis & McKelvie, 1986;Furnham & Allas, 1999;Furnham & Bradley, 1997;Furnham & Strbac, 2002). One likely explanation for this discrepancy is that the effects of auditory interference on cognitive abilities are related to task-related factors, such as the complexity of a task.…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…In general, these results stand in contrast to previous work showing that the effects of auditory interference is different for extraverts and introverts (e.g., Banbury & Berry, 1998;Belojevic et al, 2001;Cassidy & MacDonald, 2007;Daoussis & McKelvie, 1986;Furnham & Allas, 1999;Furnham & Bradley, 1997;Furnham & Strbac, 2002). One likely explanation for this discrepancy is that the effects of auditory interference on cognitive abilities are related to task-related factors, such as the complexity of a task.…”
Section: Discussioncontrasting
confidence: 55%
“…They found that introverts performed significantly poorer than extraverts on the reading comprehension task in the presence of music and noise, but that the distracting effects of music and noise were not significantly different when completing prose recall and arithmetic tasks. The contradictions between this and earlier studies (e.g., Banbury, & Berry, 1998) might be due in part to the different tasks that have been used: Konz (1962), for instance, found that music detrimentally affected a letter-matching task but not a manual assembly task (see also Furnham & Bradley, 1997). …”
Section: The Effects Of Background Auditory Interference and Personalcontrasting
confidence: 39%
See 1 more Smart Citation
“…We discovered that interference from hearing of irrelevant color words while one is naming colors decreased markedly with age. Thus, although noisy environments have been shown to disrupt adult work performance (Banbury & Berry, 1998), our results suggest that children may be even more drastically affected, for instance, by irrelevant spoken language from television or adult conversation.…”
Section: Discussionmentioning
confidence: 81%
“…To examine the effect of noise on task performance, a number of tasks, such as prose recall, serial recall or mental arithmetics are commonly used [24,38,39].…”
Section: Introductionmentioning
confidence: 99%